2012
DOI: 10.1007/s10834-012-9298-z
|View full text |Cite
|
Sign up to set email alerts
|

Couples Managing the Risk of Financing Long-Term Care

Abstract: This study examined the complexity of financial long-term care (LTC) decision outcomes among married couples. Supporting the theory of planned behavior, couples reported a range of consensus patterns with their financial LTC intentions and behaviors. Five newly articulated typologies of couples emerged from consensus patterns revealing that couples reported a range of financial LTC intentions and behaviors. More couples reported consensus with their financial LTC behaviors compared to intentions; financial LTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…These findings offer a few implications for practitioners who work with romantic couples. Due to the relational nature of navigating financial stressors within couples, these findings further encourage practitioners to work with couples and not just partnered individuals (Barnett & Stum, 2012). Most noticeably, couples with discrepant financial roles are linked with both men and women describing frequent disagreements about their finances.…”
Section: Discussionmentioning
confidence: 96%
“…These findings offer a few implications for practitioners who work with romantic couples. Due to the relational nature of navigating financial stressors within couples, these findings further encourage practitioners to work with couples and not just partnered individuals (Barnett & Stum, 2012). Most noticeably, couples with discrepant financial roles are linked with both men and women describing frequent disagreements about their finances.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to current economic circumstance, health also shapes the need for long-term care insurance (LTC). Barnett and Stum ( 2012 )’s study sought to improve understanding of the factors that influence access and coverage to long-term care insurance from a couple-level perspective. Conducting a qualitative dyadic analysis of married couples in Minnesota, the study revealed substantive consensus among couples in terms of their LTC intentions, but heterogeneity was also found in terms of their decision outcomes, such as the decision of whether to purchase LTCI, self-insure, or take no action.…”
Section: Impact Of Health On Economic Circumstancesmentioning
confidence: 99%
“…Additionally, research underscores the influence that younger generations can have on older adults’ LTCI purchase decisions, both positive and negative (Brown et al, 2012; Sperber et al, 2014), and how demographic shifts have changed aging in families and recently created more complex and diverse family structures (Hareven, 1994). Barnett & Stum’s (2012, 2013) research on future LTC planning reminds us that couples often make LTC planning decisions in concert, adding multiple individuals’ experiences. Some literature on LTCI purchase decisions incorporates socioeconomic contextual factors such as perceptions of an unstable insurance market (Curry et al, 2009) or integrates the socioeconomic context into other theoretical models to understand an individual’s LTCI purchase decision (Schaber & Stum 2007).…”
Section: Introductionmentioning
confidence: 99%